Integrating Inclusive Education and Islamic Ethical Values in The Tarbiyah Curriculum in The Era of Artificial Intelligence - Nashir, Muhammad Jafar; Amin, Lailla Hidayatul; Mukhlisah, Iffah; Trisnawati, Septian Nur Ika; Apriliani, Elina Intan (Universitas Muhammadiyah Surakarta, 2025)
The rapid advancement of artificial intelligence (AI) has reshaped educational practices, including teacher education in Islamic higher education institutions. These developments necessitate the integration of technological innovations into the Tarbiyah curriculum while upholding the principles of inclusive education and Islamic ethical values. This study examines how inclusivity and Islamic ethical values are integrated into the Tarbiyah curriculum in the era of AI, and identifies the need for a comprehensive curriculum review. Using a qualitative approach, this study involved lecturers and prospective teachers at the Faculty of Tarbiyah of an Islamic higher education institution in Indonesia. Data were collected through in-depth interviews, classroom observations, and analysis of curriculum documents, and were then thematically analyzed. Findings indicate that while awareness of inclusive education and Islamic ethical values (such as justice (‘adl), compassion (rahmah), and human dignity (karāmah al-insān)) has increased, integration of these values into the curriculum remains fragmented and unsystematic. Lecturers and students noted that AI could support differentiated learning and greater accessibility; however, they also expressed ethical concerns, including algorithmic bias, over-reliance on technology, and potential weakening of teacher–student relationships. These findings highlight structural gaps in curriculum implementation and a misalignment between technological adoption and underlying ethical–pedagogical foundations. They underscore the urgent need for a curriculum review that systematically integrates technological competence with inclusivity and Islamic ethical responsibility. This study’s main contribution is a novel integrative conceptual framework linking inclusive education, Islamic ethical values, and AI utilization within the Tarbiyah curriculum. This framework provides a basis for developing a revised curriculum that prepares future teachers to be pedagogically competent, ethically grounded, inclusive, and socially responsible in the AI era.